The impact of chronic non-specific cough on children and their families: A narrative literature review. (March 2020) - Waring, Gill; Kirk, Susan; Fallon, Debbie
The aim of this article is to critically appraise and synthesize research that examines the impact chronic non-specific cough has on children and their families and to highlight gaps within the research. Chronic non-specific cough refers to a persistent cough without a specific diagnosis. While studies have begun to examine the impact on children and their families, this research has not been synthesized and appraised. A narrative literature review was undertaken. A comprehensive and systematic search was undertaken, using CINAHL, MEDLINE, British Nursing Index, PsycINFO, Cochrane Wiley Library and ASSIA databases. Studies were critically appraised for quality using the Hawker et al.'s appraisal tool. A narrative review of the findings was undertaken. Nine quantitative studies were included in the review. The article suggests that chronic non-specific cough affects the quality of life of both families and children, affecting quality of sleep, impacting upon participation in activities, causing emotional distress and creating substantial demand on the health service. Furthermore, the research highlighted the worries experienced by parents in relation to the cause of their child's cough. The review did not identify any qualitative research in this area and only one study collected data directly from children.